ChemInform Abstract: Synthesis of Bis(indolyl)methanes Using Ammonium Niobium Oxalate (ANO) as an Efficient and Recyclable Catalyst. Issue 50 (December 2015) - Mendes, Samuel R.; Thurow, Samuel; Penteado, Filipe; da Silva, Maite S.; Gariani, Rogerio A.; Perin, Gelson; Lenardao, Eder J.
Abstract: Two procedures are applied to the preparation of bisindolylmethanes in green solvents using ammonium niobium oxalate as catalyst.